2006
DOI: 10.1007/s00436-006-0339-0
|View full text |Cite
|
Sign up to set email alerts
|

Excreted/secreted glycoproteins of G. intestinalis play an essential role in the antibody response

Abstract: In the present work, glycoproteins in the excretory/secretory products of G. intestinalis were identified and the reactivity in serum of immunized mice with these molecules was evaluated by western blotting before and after chemical treatment or enzymatic deglycosylation. Glycoproteins of 58 and 63 kDa were revealed in E/S products after periodic acid-Schiff (PAS) stain. Studies of carbohydrate specificity using digoxigenin-labeled lectins, revealed the presence of O-glycans and N-glycans. Chemical treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Excretory–secretory products were obtained from G. lamblia as described by Jimenez et al. (15). Trophozoites cultured for 48 h at 37°C in TYS‐33 medium were rinsed with warm and serum‐free RPMI‐1640 medium (Sigma, St. Louis, MO, USA) three times to eliminate nonattached or dead trophozoites.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Excretory–secretory products were obtained from G. lamblia as described by Jimenez et al. (15). Trophozoites cultured for 48 h at 37°C in TYS‐33 medium were rinsed with warm and serum‐free RPMI‐1640 medium (Sigma, St. Louis, MO, USA) three times to eliminate nonattached or dead trophozoites.…”
Section: Methodsmentioning
confidence: 99%
“…Oral administration of G. lamblia ESPs into BALB/c mice stimulated a Th2 response, which led to intestinal histological changes characterized by eosinophilic infiltration, hypercellularity, and enterocytic desquamation (14). Glycoproteins in G. lamblia ESP were found to induce antibody production during giardiasis (15,16). Cysteine proteases present in G. lamblia ESP were essential to the induction of antibody and cytokine production in BALB/c mice infected with ESP (17).…”
Section: Introductionmentioning
confidence: 99%
“…Oral administration of G. lamblia ESPs into BALB/c mice stimulated a Th2 response, which led to intestinal histological changes characterized by eosinophilic infiltration, and can induce host cell apoptosis, hypercellularity, and enterocytic desquamation (Jiménez et al, 2004). Glycoproteins in G. lamblia ESP were found to induce antibody production during giardiasis (Jiménez et al, 2007). Cysteine proteases present in G. lamblia ESP were essential for the induction of antibody and cytokine production in BALB/c mice infected with ESP (Jiménez et al, 2009).…”
Section: Exosome and Microvesicles Content Can Alter Neighbouring Cellsmentioning
confidence: 99%
“…However, recent studies have shed light on trophozoites excreted/secreted proteases and their involvement in immunological and pathophysiological processes (Jiménez et al 2000;Kaur et al 2001;Shant et al 2002, Jiménez et al 2004. A series of studies have reported that trophozoite proteins are excreted and secreted during in vitro growth (Nash and Keister 1985;Jiménez et al 2000;Shant et al 2002) and some of them have provided considerable evidences that these molecules seem to be important in processes such adhesion, nutrition, pathogenesis, and evasion of the host immune response (Kaur et al 2001;Shant et al 2002;Jiménez et al 2004;Rodríguez-Fuentes et al 2006;Jiménez et al 2007).…”
Section: Introductionmentioning
confidence: 98%